Acute and Sub-Acute Toxicity Study of Ethanolic Crude Extract of Mitracarpus hirtus Plant on Wistar Rats - Birninkudu, Ado Aminu; Oloro, Joseph; Odda, John (International Journal of Science and Healthcare Research, 2017)
Background: Plants are still considered among the important source of bioactive compound, especially in traditional medicine that has been used for centuries. Ethno botanical survey showed that Mitracarpus hirtus is used for the treatment of microbial infections, skin disease and ulcer. However, the is hardly a published on safety regarding to this herb, which may cause clinical challenges. Objective: The aim of this study was to determine the acute and sub-acute toxicity of Mitracarpus hirtus plant. Methods: Mitracarpus hirtus was obtained, dried under normal room temperature. Extraction was performed by macerating process. We used Miller and Tainter (1944) method adopted for acute toxicity study. Sub-acute study was carried out according to the OECD 407 guidelines for 28days repeated dose in rat’s models. The results were presented as Mean and SD, One Way Analysis of Variance (ANOVA) was used, followed by Turkey’s post-hoc test to determine the final significance (p≤0.05). Results: The acute toxicity result from this study showed LD50 greater than 5000mg/kg. For sub-acute, significant increase of ALP, ALT and CREAT, and decreased of AST, LDL and LDH was observed on biochemical parameters. While hematological parameters WBC, PLT, MONO and NEU values showed decrease and others were within normal range. Histopathology of liver and kidney revealed normal structure. Conclusion: the acute toxicity study showed LD50 greater than 5000mg/kg. Sub-acute toxicity study showed increase of ALT, ALP and CRET in some groups, but decrease of AST, LDH and LDL were observed, while WBC, PLT, MONO, and NEU showed decrease, while others not affected in all the treated groups. Histology of kidney and liver revealed normal structure. Concluded that the extract is relatively safe at lower concentrations.
Keywords: Mitracarpus hirtus herbs; Lethal dose; Biochemical; Hematological and histopathological parameters